A construção do discurso de autolegitimação do Jornalismo: uma investigação das campanhas publicitário-editoriais contra as "fake news" - MIRIAM CRISTINA IBANHES (2020)
This work aims to analyze the discourse of self-defense and self-legitimation in the journalistic field in the face of the contemporary phenomenon of mass dissemination of the so-called "fake news". Worsened by the contemporary technological scenario and the role of an audience that was previously understood as refractory, the hypothesis arises that the field is unable to respond and find solutions that mitigate the loss of credibility, ending up seeking defense in a self-referential discourse anchored in a “naive realism” (GOMES, 2009), based on the traditional precepts of objectivity and truth, without taking into account the fact that the events narrated by Journalism refer, as a rule, to information that is attributed to third parties (KOCH, 1990), creating “real effects” (CHARAUDEAU, 2018). By clinging to precepts that have been questioned since the 19th century, Journalism ends up weakening its own self-legitimation, insofar as it bases its self-referential discourse on the same elements it fights. This dissertation uses, methodologically, the concept of ethos from the perspective of Maingueneau (2013; 2019), as well as its constitutive characteristics - pre-discursive ehtos, discursive ethos, said ethos, shown ethos and scenography - to unveil the discursive strategies (and their eventual gaps and contradictions) in the construction of the discourse of self-defense and self-legitimation of Journalism. As a result of this research, it is expected to identify in the analyzed advertising campaigns some of the tactics of convincing and engaging used by fake news, as a strategy to shape the place of speech of Journalism before its audience.